2018
DOI: 10.1016/j.jth.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Are head injuries to cyclists an important cause of death in road travel fatalities?

Abstract: Background: Despite the well-recognised benefit for individuals and communities of increased active travel, cycling remains a minority travel mode in many high income countries. Fear of injury is often cited as a reason. Campaigns to promote cycle helmet wear are alleged to contribute to this. However, there is little information on whether head injuries to cyclists are an important cause of death in road travel fatalities, compared with other road users. Methods: We examined secondary causes of death for road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Individuals involved in road crashes with high injury severity levels are strongly correlated with death outcomes; road victims with reportedly high injury severity scores (i.e., ISS 51-75) suffer from low survival rates compared to victims with a low ISS score of 40 or less [41]. Several studies confirmed the strong association between fatal road crashes and severe head trauma, particularly among pedestrians and motorcyclists [32,42]. Head injuries are considered a severe injury, leading to 4-5 times higher risk of road deaths.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Individuals involved in road crashes with high injury severity levels are strongly correlated with death outcomes; road victims with reportedly high injury severity scores (i.e., ISS 51-75) suffer from low survival rates compared to victims with a low ISS score of 40 or less [41]. Several studies confirmed the strong association between fatal road crashes and severe head trauma, particularly among pedestrians and motorcyclists [32,42]. Head injuries are considered a severe injury, leading to 4-5 times higher risk of road deaths.…”
Section: Discussionmentioning
confidence: 95%
“…The study findings align with existing studies and reveal that 'crash type', mainly the 'vehicle-pedestrian' and the 'truck-motorcycle' types were the most significant factors associated with the increased risk of road fatalities. This is evident as pedestrians and motorcyclists are particularly vulnerable road users [32]. Studies in many low-and middle-income countries (LMICs) indicate that pedestrians disproportionally account for the majority of road fatalities [1], particularly that a large number of individuals commute by walking-the most affordable mode of transportation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple injuries were prevalent among pedestrians and drivers. 44 Almost all patients (90.3%) attained a recovered or improved status upon discharge in our PGH study. However, 4.7% had unchanged status from admission to discharge, while 3.5% died in the hospital.…”
Section: Road Crash Deathsmentioning
confidence: 67%
“…The head is a frequently injured body region in cyclists where severe head injuries can lead to cause of death in this population [1][2][3][4]. Children appear to be overrepresented and at greater risk than adults [4,5].…”
Section: Introductionmentioning
confidence: 99%